REVITALISASI PEMUDA DEMI MEMAJUKAN INDONESIA - Widodo, Sumardi (Faculty of Humanities, Diponegoro University, 2011)
The progress of civilization is always determined by the active role of the young generation. There are special qualities inherent in youth that makes young people incomparably necessary as social agent of change. Through various teachings of Quran and eminent Islamic thinkers, we can draw several wise advised about how to create a better young generation. Self-introspection, alignment to noble morality, courageous life, and persistence in pursuing what the goals we deem life-worth are explained. Â Keywords: youth, agent of change, Islamic values